2019
DOI: 10.31557/apjcp.2019.20.2.327
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Omega-3 Fatty Acids in Fish Consumption Against Breast Cancer in Asian Patients: A Meta-Analysis

Abstract: Objective:This systematic review and meta-analysis was performed to determine the protective effect of omega-3 fatty acids in fish consumption against breast cancer in Asian patients. Methods:The authors conducted a meta-analysis of published research articles on protective effect of omega-3 fatty acids in fish consumption against breast cancer in Asian patients published between January 2000 and July 2018 in online database of PubMed, ProQuest and EBSCO. Pooled odds ratios (OR) were calculated by using fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 29 publications
2
30
0
3
Order By: Relevance
“…No associations were found between consumption of eicosapentaenoic acid, docosahexaenoic, or α‐linolenic acid and BC incidence. Studies with Eastern Asian populations confirmed the association between higher consumption of fish n ‐3 PUFA and reduced BC incidence (RR = 0.80; Nindrea et al, ).…”
Section: Dietary Fat and Breast Cancer (Bc)mentioning
confidence: 81%
See 1 more Smart Citation
“…No associations were found between consumption of eicosapentaenoic acid, docosahexaenoic, or α‐linolenic acid and BC incidence. Studies with Eastern Asian populations confirmed the association between higher consumption of fish n ‐3 PUFA and reduced BC incidence (RR = 0.80; Nindrea et al, ).…”
Section: Dietary Fat and Breast Cancer (Bc)mentioning
confidence: 81%
“…Two studies included in this review demonstrated a positive association between higher consumption of PUFA and risk of post‐menopausal BC, however, these studies did not differentiate between n ‐3 and n ‐6 PUFA in the analysis. On the other hand, higher consumption of marine n ‐3 PUFA has been shown to be inversely associated with BC incidence (Nindrea et al, ; Zheng et al, ). Moreover, a higher ratio of n ‐3/ n ‐6 is also considered to be protective (Alarcon de la Lastra, Barranco, Motilva, & Herrerias, ; Yang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…High fibre intakes, particularly from cereals or grains and fruit, are associated with a reduced risk of incident colorectal adenoma and cancer [8], [12], [23]. Prospective study within a population-based screening trial suggests that individuals consuming the highest intakes of dietary fibre have reduced risks of incident colorectal adenoma and distal colon cancer and that this effect of dietary fibre, particularly from cereals and fruit, may begin early in colorectal carcinogenesis [11], [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the role that omega-3 fats in fish oil play in tumor suppression continues to be investigated, and more interventions are needed on omega-3 dosage and subtypes (DHA versus EPA) [47]. Further, European and Asian cohorts have recorded possible risk reduction of colorectal and breast cancers with omega-3 fish consumption [48,49], but more research is needed in Blacks. Brasky et al found no significant association between omega-3 and fish consumption and endometrial cancer risk in 47,602 African American women, although non-significant hazard ratios were more favorable among normal weight women (HR = 0.53; 95% CI = 0.18, 1.58) than in overweight women (HR = 0.88; 95% CI = 0.56, 1.31) [50].…”
Section: Cancermentioning
confidence: 99%